Penyuluhan Hukum Tentang Memahami Hukum Perbankan Pada Perlindungan Konsumen Dan Praktik Yang Adil Di Kecamatan Cilongok Kabupaten Banyumas - Wiwin Muchtar Wiyono; Doni Adi Supriyo; Teguh Anindito (Universitas Wijayakusuma Purwokerto, 2026)
.Legal counseling is a form of community service aimed at increasing public awareness and understanding of their legal rights and obligations in various aspects of life, including in the banking sector. The legal counseling activity, entitled